Peran Pendidikan Agama Islam dalam Membentuk Karakter dan Etika Siswa di Madrasah Aliyah Al-Hikmah Ciruas Serang Banten - Nakhma’ussolikhah Nakhma’ussolikhah; Ficky Adi Kurniawan; Mustain Mustain; Ilsa Iman Nulloh; Ummul Bariroh; Elok Faiqoh El Chaziem; Alwan Alwan; Abdullah Abdullah; Nur Asiyah; Muhammad Husni Mubarok As; Cirkam Cirkam (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to examine in depth the role of Islamic Religious Education (PAI) in shaping the character and ethics of students at Madrasah Aliyah Al-Hikmah, Ciruas, Serang, Banten. Amidst the challenges of globalization and modernization that bring changes in values and behavior, PAI plays a strategic role in instilling moral, spiritual, and social values in students. Religious education not only teaches religious knowledge but also shapes attitudes, behaviors, and mindsets in accordance with Islamic teachings, enabling students to cope with diverse environmental influences. This study uses a qualitative descriptive approach with data collection techniques through observation, in-depth interviews, and documentation studies. Research informants consisted of PAI teachers, students, the principal, and homeroom teachers, thus obtaining a comprehensive picture of the implementation of PAI at the madrasah. The results show that PAI makes a significant contribution to the formation of student character, particularly in aspects of religiosity, discipline, responsibility, honesty, tolerance, and courtesy. Learning strategies used include habituating worship, teacher role models, enforcing school rules, and integrating Islamic values into all subjects. Additionally, extracurricular activities such as religious study groups, Islamic holiday commemorations, and Quran memorization programs are also effective tools for strengthening students' character. However, this study also identified several challenges, including low parental involvement in children's character development, negative environmental influences, and limited variety of learning methods. Therefore, synergy between madrasahs, families, and the community is needed to create an educational ecosystem that supports comprehensive and sustainable character development. Through this collaboration, Islamic Religious Education (PAI) is expected to provide a strong foundation for creating a generation with noble character and competitiveness in the modern era.